Stability and seasonal adaptability of sugarcane (Saccharum officinarum)clones across crop cycles revealed by AMMI analysis - ADILAKSHMI, D; PADMAVATHI, P V; RAO, D PURUSHOTAMA (The Indian Journal of Agricultural Sciences, 2026)
Sugarcane (Saccharum officinarum L.) productivity in Andhra Pradesh has declined due to seasonality and the scarcity of stable high-performing sugarcane clones. Thus, the identification of sugarcane genotypes that perform consistently in the fields across several cropping seasons and exhibit good quality parameters is of primary interest for sustainable development of sugarcane varieties. The field experiment was conducted for three years from 2022 to 2024 at the Regional Agricultural Research Station, Anakapalle, Visakhapatnam, Andhra Pradesh to assess 20 sugarcane genotypes, 14 test clones and six standard checks across three crops cycles, viz. first crop, second crop and ratoon using a randomised block design (RBD) plot arrangement with three replications. The joint analysis of seasonal variance and AMMI (Additive Main effects and Multiplicative Interaction) analysis indicated significant individual effects attributable to genotype (G), environment (E) and their interaction (GEI) for all traits examined in this investigation. Genotypic effects were predominant in variation for cane yield and sugar yield traits: cane yield (34.34%), CCS (Commercial cane sugar) yield (36.38%) and CCS% (33.72%) than environmental effects (20.58% cane yield, 10.37% CCS yield and 9.17% CCS % variation), highlighting the predominance of genetic control. Based on their mean performance, three entries 2018A 6, 2018A 157 and 2018A 88 were identified as superior clones for cane yield and sucrose accumulation. The AMMI model identified clones 2018A 157 and 2018A 88 as potential stable clones for cane yield. Additionally, clones 2018A 157 and 2018A 6 were found to be promising for CCS yield, while clone 2018A 6 was identified as the ideal clone for sucrose % and CCS % . Overall, clones 2018A 157 and 2018A 6 emerged as the most ideal genotypes, combining high performance and stability across all traits. Furthermore, the AMMI stability value indicated that clones 2018A 107 and 2018A 130 were stable across crop cycles for all evaluated traits.